PUBLIC-PRIVATE PARTNERSHIP PROCUREMENT TRANSPORT INFRASTRUCTURE DELIVERY: ASSESSING THE MANAGERIAL CAPABILITIES OF PUBLIC-SECTOR ORGANIZATIONS IN AFRICA - Betty Oluwafunso OLOJEDE (Scientific Journal of Silesian University of Technology. Series Transport)
The lingering imbalance between infrastructural services demand and supply poses serious threats to the fiscal budget balance from contingent liabilities of African countries. Despite the increasing private investment commitments and adoption of public-private partnership procurement (PPP) options to address the widening infrastructure gaps in Africa, the failure in the delivery of public infrastructure projects is yet a common phenomenon. This study therefore examined the managerial capabilities of public-sector organizations (PSOs), who steer the provisions of public infrastructure, to investigate their readiness to achieve the value for money from private funding and the benefits of PPP options. The study conducted a self-study structured questionnaire survey on professionals in PSOs in Africa, particularly Nigeria, who have been directly involved in the delivery of public infrastructure projects via PPP. The professionals were purposively sampled and the primary data obtained was subjected to descriptive and inferential analysis. The study revealed that the PSOs have internalized about 41 PPP-capabilities for the delivery of public infrastructure projects. Up to 40 PPP-capabilities were exhibited on an average score (41-60%) level, with mean score (MS) value range of 3.13 ≤ MS ≤ 3.70, for the public projects procured. The study established the existence of significant interdependence of p < 0.001, which indicated sufficient correlation between 31 PPP-capabilities and explained the 10 main components of managerial capabilities possessed by the PSOs. Some of the components clustered around public infrastructure planning and adaptability to PPP programme, project delivery parameters and control, suitable public infrastructure procurement knowledge, public policy awareness and innovation, and governance. The study provides information crucial for public infrastructure delivery success towards sustainable national economic recovery and development.